2015
DOI: 10.1186/s12889-015-2003-z
|View full text |Cite
|
Sign up to set email alerts
|

HIV, Hepatitis B and C among people who inject drugs: high prevalence of HIV and Hepatitis C RNA positive infections observed in Delhi, India

Abstract: BackgroundIndia has large PWID (persons who inject drugs) population estimated at 177,000. PWIDs are at high risk for HIV, Hepatitis B (HBV) and Hepatitis C (HCV) infections. We report the prevalence of HIV, HBV and HCV infections and correlates of HIV-HCV co-infection among male PWIDs in Delhi.Methods3748 male PWIDs were recruited for a longitudinal HIV incidence study. Participants were tested for HBV and HCV infections at their first follow-up visit (FV1) using serum HBV-surface antigen, and HCV-antibody te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
31
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 22 publications
3
31
0
1
Order By: Relevance
“…This high rate confirms that, as it is well-known, PWID are one of the most important and high-risk groups for developing HCV [2,71]. The prevalence of HCV among PWID in Iran was lower than the rate reported in other countries, including South Africa (55%) [72], Pakistan (72%) [73] and India (53.7%) [74] but higher than in studies conducted in Kuwait (12.28%) [4], Kingdom of Saudi Arabia (42.7%) [75], and Brazil (35.6%) [76]. These differences in prevalence can be attributed to Fig.…”
Section: Discussionsupporting
confidence: 70%
“…This high rate confirms that, as it is well-known, PWID are one of the most important and high-risk groups for developing HCV [2,71]. The prevalence of HCV among PWID in Iran was lower than the rate reported in other countries, including South Africa (55%) [72], Pakistan (72%) [73] and India (53.7%) [74] but higher than in studies conducted in Kuwait (12.28%) [4], Kingdom of Saudi Arabia (42.7%) [75], and Brazil (35.6%) [76]. These differences in prevalence can be attributed to Fig.…”
Section: Discussionsupporting
confidence: 70%
“…[88][89][90][91][92][93] A high prevalence of HCV and HIV coinfection has been found in intravenous drug users ranging from 13.2% to 86%. [94][95][96][97] HIV-infected patients with HCV coinfection have a faster progression to AIDS and slower CD4+ recovery than patients with HIV infection alone as was shown in the Swiss Cohort study. 98 There is a better immunological response to HAART in HIV-infected patients without HCV than in the coinfected patients.…”
Section: Management Of Hcv In Hiv Coinfectionmentioning
confidence: 99%
“…The rate of HBsAg positivity was reported earlier as 2.7–10.8% among intravenous drug users, 1 but in more recent studies it was reported as 7% in Chennai, 95 9.7% in Delhi 96 and 5.1% in another region. 97 In an area reported with highest drug abuse, occult infection was found in 15.9%.…”
Section: Hepatitis B In Special Populationsmentioning
confidence: 90%